KEBEBASAN BEREKSPRESI PERSEPEKTIF HAK ASASI MANUSIA: Freedom Of Expression From A Human Rights Perspective - Puspa, I Wayan; Suradana, I Made; Subardan, Ismak (Ganec Swara, 2025)
Freedom of expression is a universal right that must be enjoyed by everyone, but this freedom of expression is not unlimited or absolute. Therefore, it requires regulation in both international instruments and national human rights instruments. The problem in this study is: "How is the regulation of freedom of expression in international instruments and national human rights instruments"? This research is a normative legal research. The approaches used are the statute approach and the conceptual approach. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The collection of legal materials was carried out by document study, while the analysis of legal materials used qualitative descriptive analysis. The results of the study show that the regulation of freedom of expression is regulated both in international human rights instruments (the Universal Declaration of Human Rights and the Covenant) and in national human rights instruments (the 1945 Constitution of the Republic of Indonesia and other laws and regulations). The regulation of freedom of expression is so important. Freedom of expression is one of the absolute requirements that allows democracy and public participation in decision-making. Freedom of expression is a prerequisite for the realization of the principles of transparency and accountability which are ultimately very important for the advancement and protection of human rights.